Asthma Control in Canada Remains Suboptimal: The Reality of Asthma Control (TRAC) Study - J Mark FitzGerald; Louis-Philippe Boulet; R Andrew McIvor; Sabrina Zimmerman; Kenneth R Chapman (Canadian Respiratory Journal)
BACKGROUND: Two Canadian studies showed that 55% of patients with asthma had daily symptoms (in 1996) and that 57% of patients suffered from poorly controlled asthma (in 1999).